Protein Urine Sebagai Penanda Preeklampsia Dalam Kehamilan - Antu, Yuniarty (Program Studi DIV Kebidanan Fakultas Ilmu Kesehatan Universitas Muhammadiyah Gorontalo, 2024)
Maternal mortality rate in Indonesia still high and the prevalence of perinatal deaths is four times higher in cases of preeclampsia/eclampsia. Urine protein tests still used to assess preeclampsia in pregnant women. This study aimed to evaluate proteinuria in pregnant women-based parity, age and weeks of pregnancy in Gorontalo. This study used descriptive with cross sectional study based on inclusion and exclusion criteria. The results showed that 50% of subjects experienced proteinuria with values of +1 (45.8%) and +2 (4.2%). The high incidence of proteinuria in pregnant women means that urine protein tests as easy and fast methods help to detect preeclampsia in pregnant women.